Future Challenges in the Framework of Integrated and Sustainable Environmental Planning: Case Studies and Innovative Proposals (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The correct management of territory and its planning based on scientific criteria in the face of the anthropogenic impacts of human activities is one of the main challenges in the 21st century. This publication includes some of the latest advancements in environmental planning and spatial analysis related to the ecological management of territory from a multidisciplinary perspective. The research papers from different researchers, scholars and experts in this field included in this collection were published by the International Journal of Environmental Research and Public Health after undergoing a rigorous anonymous peer review process.